Review of the current understanding of the treatment of the isolated systolic hypertension in young and middle-aged adults - Svyntozelska, O. O. (Запорізький державний медичний університет, 2021)
Objectives: This study aims to assess the current knowledge and understanding of the treatment of isolated systolic hypertension (ISH) in young and middle-aged adults. Methods: In this review, PubMed, Scopus, and the WoS databases were searched from January 1, 2010, to January 1, 2020, using systolic hypertension and hypertension in young as keywords. Two researchers conducted the searches, screenings, quality assessments, and data extractions separately. Objectives: This study aims to assess the current knowledge and understanding of the treatment of isolated systolic hypertension (ISH) in young and middle-aged adults. Methods: In this review, PubMed, Scopus, and the WoS databases were searched from January 1, 2010, to January 1, 2020, using systolic hypertension and hypertension in young as keywords. Two researchers conducted the searches, screenings, quality assessments, and data extractions separately.